ANGIOTENSIN RECEPTOR BLOCKERS WITH PLEIOTROPIC PROPERTIES: A NEW STANDARD IN CARDIOVASCULAR RISK MANAGEMENT AND TREATMENT OF HYPERTENSION - V. I. Podzolkov (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2017)
An increase in the activity of the renin-angiotensin-aldosterone system is one of the most important mechanisms for the realization of the cardiovascular continuum. The role that angiotensin receptor blockers play in achieving target figures of blood pressure and reducing cardiovascular risk is discussed. The importance of pleiotropic properties of angiotensin receptor blockers (in particular, activation of peroxisome proliferator-activated receptors gamma – PPAR-γ) in the management of patients with insulin resistance, obesity, dyslipidemia is also covered. The evidence base for the use of telmisartan as a drug with pleiotropic effect in patients with arterial hypertension and associated diseases (diabetes mellitus, obesity, renal dysfunction) is discussed.